(untitled) (TAMADDUN NURI JURNALI, 2025)
This article is devoted to the study of speech strategies and tactics used by lawyers during court proceedings. The research analyzes the speech strategies and tactics of Kazakhstani lawyers A.T.Shaikhina, T.M.Sisenbayev, M.K.Tuleev, and Zh.S.Sarmanov, based on their speeches during the debates in the trial of former Supreme Court judges Tashenova and Dzhakishev. The analysis revealed that each of the mentioned lawyers employed a unique set of various strategies and tactics.